Azhe'é Bidziil (Strong Fathers): Study Protocol for the Pilot Evaluation of an American Indian Fatherhood Program to Improve the Health and Wellbeing of Diné (Navajo) Fathers - Richards, Jennifer; Begay, Tiffani; Chambers, Rachel A.; Patel, Hima; Mayhew, Justin; Allison-Burbank, Joshuaa; Gishie, LeDaniel; Tsingine, Nolan; Badoni, Julius; Staley, Leander; Harvey, Bradlin; Tsosie, Alicia; et al. (Frontiers in Public Health, 2022)
Introduction Considering the critical role that American Indian and Alaska Native (Native) men play in family and child health, there is an urgent need to collaborate with Native communities in developing interventions and policies to improve Native men's health status. This study aims to address a significant gap in research by designing and implementing a culturally grounded health promotion program to increase economic stability, promote positive parenting, and build healthy relationships among Native fathers. The Azhe'é Bidziil (“Strong Fathers”) study protocol, developed in response to community advisory board feedback, illustrates a community-engaged approach to developing and implementing a fatherhood program in two Diné (Navajo) communities. Methods/Analysis Azhe'é Bidziil was adapted from three evidence-based interventions developed in collaboration with Native communities. Intervention lessons were iteratively reviewed by a tribal working group to ensure that the content is culturally appropriate and relevant. A pre-post study will assess feasibility, acceptability, and satisfaction with the Azhe'é Bidziil intervention, as well as short-term impacts on positive parenting, economic stability, and healthy relationship outcomes. The intervention is composed of 12 weekly group sessions conducted with fathers (n = 750) that focus on developing knowledge and skills for positive father involvement, economic stability, and healthy relationships. Lesson content includes: honoring our roles as fathers, building healthy relationships, understanding the impact of historical trauma, goal-setting, and budgeting basics. Each of the 12 group lessons, consisting of 8–12 participants per group, last approximately 2 h. Eligible fathers or father figures are age ≥18 years, live within 50 miles of the participating Diné communities, and must be caregivers of at least one child ≤ 24 years. The outcomes for this study are acceptability, feasibility, and satisfaction with the intervention, as well as father involvement, quality of (co-) parenting communication, healthy relationships, fathers' engagement and communication with their children, protective factors (e.g., cultural connectedness and educational/career aspirations), and economic empowerment and stability. Participants will complete an outcome assessment at pre- and post-intervention (12 weeks later). Discussion This study protocol presents one of the few evaluations of a fatherhood intervention to increase economic stability, promote positive parenting, and build healthy relationships among Native fathers in rural tribal communities. Such a study is sorely needed to address the health disparities perpetuated by social and Indigenous determinants of health that Native men experience today. If proven efficacious, this pre- post-study will inform a large scale randomized controlled trial to evaluate intervention impact, and if proven efficacious may be disseminated widely in tribal nations. Study findings may also deepen our understanding of peer mentoring, Native men's health status, involvement with their children, co-parenting relationships, family relationships, cultural connectedness, and economic status. The data collected may also inform strategies to ensure acceptability, feasibility, and satisfaction of an intervention designed specifically for Native fathers.